The Effect Of Antioxidant (Alpha-Tocopherol) Addition In Preservation Medium On Follicle Diameter And Oocyte Quality After Local Sheep Ovary Preservation - Faradana, Najma Rika; Widyastuti, Rini; Setiawan, Rangga (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This study aimed to evaluate the effect of adding the antioxidant Alpha-Tocopherol to the preservation medium on follicle diameter and oocyte quality of local sheep ovaries after 24 hours of storage at 4–5°C. The ovaries were divided into four treatment groups: P1 (dPBS), P2 (dPBS + 200 µM H₂O₂), P3 (dPBS + 200 µM H₂O₂ + 3 mM alpha-tocopherol), and P4 (dPBS + 3 mM alpha-tocopherol). The results showed no significant differences in follicle diameter changes among all treatments. The addition of Alpha-Tocopherol also did not demonstrate a notable effect in maintaining oocyte quality. Oocytes collected from all treatment groups exhibited relatively similar percentages of grade 1, 2, and 3. This study indicates that Alpha-Tocopherol does not provide a significant protective effect on follicle diameter or oocyte quality during short-term ovary preservation.